Unveiling Healthcare Disparities: Social Exclusion and Public Health Challenges in Rural Ganderbal, Kashmir - Hamid, Snober; Hussain Sheikh, Aasif; Amreen, Amreen (Journal of Community Medicine and Health Solutions, 2025)
This study explores the dynamics of social exclusion in healthcare settings within the rural Ganderbal district of Kashmir, focusing on the availability of health facilities and the health-seeking behaviors of socially disadvantaged populations. Through a mixed-methods approach, combining quantitative data from interviews and qualitative insights from observation, the research reveals significant disparities in healthcare access between rural and urban areas. Key findings indicate that rural residents face exclusion due to a scarcity of hospitals, unavailability of 24-hour medical staff, inadequate infrastructure, staffing shortages, and systemic biases, compounded by environmental and occupational challenges. Communicable diseases predominate, with majority of respondents affected, and traditional healers and medical shops serve as primary care sources over formal institutions like government hospitals. Socio-economic factors, including low literacy, reliance on agriculture, and poverty, exacerbate these issues. The study highlights higher infant mortality and malnutrition rates in rural areas compared to urban centers, underscoring the need for attitudinal shifts among healthcare providers and systemic improvements in infrastructure and policy to enhance health equity. By addressing an underexplored gap in rural health research in India, this work aims to inform strategies for inclusive healthcare delivery, potentially yielding broader societal benefits through improved well-being and demographic dividends.